2020
DOI: 10.1515/ijfe-2020-0152
|View full text |Cite
|
Sign up to set email alerts
|

Screening and characterisation of β-glucosidase production strains from Rosa roxburghii Tratt

Abstract: The β-glucosidase properties from one yeast isolate identified as Wickerhamomyces anomalus C4 were characterised. The β-glucosidase activity of W. anomalus C4 was 41.83 ± 0.25 mU/mL, and the optimum temperature and pH were 40 °C and 5.0, respectively. The glucose, 10% v/v of ethanol and 10 mmol/L of Cu2+ inhibited the β-glycosidases activities. The isolate W. anomalus C4 had a stronger alcohol metabolism capacity than commercial Saccharomyces cerevisiae X16. Besides, fermentation with W. anomalus C4 alone and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Compared with SCw (0.68 g/L), the volatile acids in wines (0.49–0.65 g/L) with added β-glucosidase, except H-Ew (0.68 g/L), decreased, which had no relation with the adding strategies of β-glucosidase ( Table 2 ). The volatile acid content of wines also decreased after being fermented by yeast strains with β-glucosidase activity [ 20 , 21 ]. Excessive volatile acids (>1.2 g/L) would bring undesirable flavors to wine [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with SCw (0.68 g/L), the volatile acids in wines (0.49–0.65 g/L) with added β-glucosidase, except H-Ew (0.68 g/L), decreased, which had no relation with the adding strategies of β-glucosidase ( Table 2 ). The volatile acid content of wines also decreased after being fermented by yeast strains with β-glucosidase activity [ 20 , 21 ]. Excessive volatile acids (>1.2 g/L) would bring undesirable flavors to wine [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…González-Pombo et al (2011) [ 8 ] also reported that the purified β-glucosidase from I. terricola could significantly increase the content of varietal aroma compounds in white Muscat wine. It reflected that adding β-glucosidase could increase the varietal aroma content of wines, which usually exist as nonvolatile odorless glycosides, and β-glucosidase could hydrolyze the aroma compounds to release volatile aroma compounds and enhance the content of varietal aroma compounds [ 20 , 25 , 26 , 27 ]. In addition, the content of volatile aroma compounds and the number of β-glucosidase combined added in wines are directly proportional.…”
Section: Resultsmentioning
confidence: 99%
“…The must of R . roxburghii contains a variety of trace elements such as iron, zinc, and copper, in addition to abundant amino acids and vitamins [ 26 ]. These nutrients may have various impacts on the mycelial growth of P .…”
Section: Discussionmentioning
confidence: 99%
“…Even though its fruit has a sour, astringent, and bitter taste [4], coupled with low single fruit weight (ca. 15 g), short harvest time and a short storage life [5], our previous investigations have found that cili is especially suitable for making fruit wine owing to its high aroma retention and distinctive flavor [5] [Figure 1c].…”
Section: Introductionmentioning
confidence: 99%
“…Those results provided the direction for subsequent screening, in which six strains that most enhanced the aroma of fermented juice were isolated. We showed that Wickerhamomyces anomalus strain C4 had high β-glucosidase activity, which can lead to aroma enhancement [4]. Hanseniaspora uvarum strains F13 [7], F119 [8], C26, C31 and C110 [9] all had the ability to reduce the acidity and increase the aroma intensity and complexity of cili wine during laboratory-scale fermentation.…”
Section: Introductionmentioning
confidence: 99%